High Intrapatient Variability of Tacrolimus Exposure in the Early Period After Liver Transplantation Is Associated With Poorer Outcomes. Issue 3 (March 2018) - Rayar, Michel; Tron, Camille; Jézéquel, Caroline; Beaurepaire, Jean Marie; Petitcollin, Antoine; Houssel-Debry, Pauline; Camus, Christophe; Verdier, Marie Clémence; Dehlawi, Ammar; Lakéhal, Mohamed; Desfourneaux, Véronique; Meunier, Bernard; et al.
Abstract : Background: Tacrolimus (TAC) is the cornerstone of immunosuppressive regimen in liver transplantation (LT). Its pharmacokinetics is characterized by a high interpatient and intrapatient variability (IPV) leading to an unpredictable dose-response relationship. The aim of our study was to evaluate the impact of TAC IPV (IPV) on graft and patient outcomes after LT. Methods: We retrospectively analyzed 812 LT recipients treated with TAC. The IPV of TAC concentrations was estimated by calculating the coefficient of variation (CV) of whole blood trough concentrations. Patients were categorized in 2 groups: low IPV (CV < 40%) and high IPV (CV ≥ 40%). Results: There were significantly more neurologic complications (31.2% vs 16.6%, P < 0.001), cardiovascular complications (19.7% vs 9.7%, P < 0.001), and acute renal failure requiring dialysis (8.5% vs 2.2%, P < 0.001) in the high CV group than in the low CV group. Moreover, graft survival was significantly poorer in the high CV group (hazard ratio, 1.42; 95% confidence interval, 1.04-1.95; P = 0.03). A pretransplantation elevated Model for End-Stage Liver Disease score ( P < 0.001) and Child-Pugh grade ( P < 0.001) were identified as risk factors for presenting a high CV. Conclusions: A high CV of TAC concentrations was found to be predictive of TAC-related toxicity and poorer survival. Abstract : The authors of this retrospective study assessed the association between high intrapatient tacrolimus variability during the first postoperative month and liver transplant outcome measures, including graft survival and tacrolimus-related toxicities.